Jewelry box: inspired by National Library of Malaysia/ Nor Afrina Natalia Hasanal Ali - Hasanal Ali, Nor Afrina Natalia (2022)
The National Library of Malaysia is the organization in charge of maintaining the national repository of knowledge assets for current and future generations. The interior architecture is influenced by the mind concept, while the design concept is based on the traditional Malay Tengkolok. Jewelry box with Malaysian National Library as inspiration. Through ideation and idea development, the motif, shape, form, and aesthetic line "National Library of Malaysia" were transformed into the design for the National Library of Malaysia.